Verbal behaviors of teachers and student anxiety in language classes - Bekalu Atnafu Taye (College of education, Bahir Dar University, 2023)
The objectives of this study were to examine the features of teacher-student interaction and to identify dominant social factors that caused anxiety in language classes. The participants of the study were both teachers and students drawn from the Department of Foreign Languages and Literature at Addis Ababa University. The study was qualitative and it used interviews, focus group discussions and diaries. The results of the study showed that freshman students were anxious due to teachers' verbal behaviors. The data revealed that there were various social factors that let students experience anxiety of which disrespecting students by teachers was one of the most important elements. Some instructors were inconsiderate in their treatment of students. They insulted students which made students feel socially inept. In view of the above, students should be guarded against unprofessional behavior of teachers which has gripped the minds of the students.